Two Years Under Jokowi – Jokowi: King or Puppet? - Syailendra, Emirza Adi (2016)
Joko Widodo has sought to neutralise the power of oligarchs, by balancing them with other actors. How does the recalibration of Indonesia’s political dynamics shed light on Jokowi’s approach to politics? What does this mean for Indonesia’s democratic process?